Bioremediation of environmental wastes: the role of microorganisms - Ayilara, Modupe S.; Babalola, Olubukola O. (Frontiers in Agronomy, 2023)
The increasing rate of urbanization and industrialization has led to several pollutions which arise from the release of toxic chemicals to the environment by the producing industries (such as detergent and dye), agricultural sectors (e.g. fertilizers and pesticides), mining industry (e.g. cyanide and sulphuric acid) and construction companies (e.g. types of cement and metals). These pollutants have adverse effects on the health of plants, animals and humans, and they also lead to the destruction of microorganisms in both the aquatic and the terrestrial regions and have called for a need for remediation. Although different remediation methods, such as the physical and chemical methods, have been adopted for years; however, the drawbacks and challenges associated with them have promoted the use of an alternative which is bioremediation. Bioremediation involves using biological agents such as plants and microbes to remove or lessen the effects of environmental pollutants. Of the two, microbes are more utilized because of their rapid growth and ability to be easily manipulated enhancing their function as agents of bioremediation. Different groups of bacteria, fungi and algae have been employed to clean up various environmental pollutants. This review discusses the different types and mechanisms of microbial bioremediation, the factors affecting microbial bioremediation, and recommendations to help to promote the use of microbes as bioremediation agents.